Personalized probiotic strategy considering bowel habits: impacts on gut microbiota composition and alleviation of gastrointestinal symptoms via Consti-Biome and Sensi-Biome - Min, Uigi; Jin, Yoo-Jeong; Jang, You Jin; Lim, Jonghyun; Kim, Byung-Yong (Frontiers in Nutrition, 2024)
Personalized probiotic regimens, taking into account individual characteristics such as stool patterns, have the potential to alleviate gastrointestinal disorders and improve gut health while avoiding the variability exhibited among individuals by conventional probiotics. This study aimed to explore the efficacy of personalized probiotic interventions in managing distinct stool patterns (constipation and diarrhea) by investigating their impact on the gut microbiome and gastrointestinal symptoms using a prospective, randomized, double-blind, placebo-controlled clinical trial design. This research leverages the multi-strain probiotic formulas, Consti-Biome and Sensi-Biome, which have previously demonstrated efficacy in alleviating constipation and diarrhea symptoms, respectively. Improvement in clinical symptoms improvement and compositional changes in the gut microbiome were analyzed in participants with predominant constipation or diarrhea symptoms. Results indicate that tailored probiotics could improve constipation and diarrhea by promoting Erysipelotrichaceae and Lactobacillaceae, producers of short-chain fatty acids, and regulating inflammation and painassociated taxa. These findings suggest the potential of tailored probiotic prescriptions and emphasize the need for personalized therapeutic approaches for digestive disorders. Clinical Trial Registration: [https://cris.nih.go.kr/cris/index/index.do], identifier [KCT0009111].